Thyroid Hormone Upregulates Hypothalamic kiss2 Gene in the Male Nile Tilapia, Oreochromis niloticus - Ogawa, Satoshi; Ng, Kai W.; Xue, Xiaoyu; Ramadasan, Priveena N.; Sivalingam, Mageswary; Levavi-Sivan, Berta; Lin, Haoran; Parhar, Ishwar (Frontiers in Endocrinology, 2013)
Kisspeptin has recently been recognized as a critical regulator of reproductive function in vertebrates. During the sexual development, kisspeptin neurons receive sex steroids feedback to trigger gonadotropin-releasing hormone (GnRH) neurons. In teleosts, a positive correlation has been found between the thyroid status and the reproductive status. However, the role of thyroid hormone in the regulation of kisspeptin system remains unknown. We cloned and characterized a gene encoding kisspeptin (kiss2) in a cichlid fish, the Nile tilapia (Oreochromis niloticus). Expression of kiss2 mRNA in the brain was analyzed by in situ hybridization. The effect of thyroid hormone (triiodothyronine, T3) and hypothyroidism with methimazole (MMI) on kiss2 and the three GnRH types (gnrh1, gnrh2 and gnrh3) mRNA expression was analyzed by real-time PCR. Expression of thyroid hormone receptor mRNAs were analyzed in laser-captured kisspeptin and GnRH neurons by RT-PCR. The kiss2 mRNA expressing cells were seen in the nucleus of the lateral recess in the hypothalamus. Intraperitoneal administration of T3 (5µg/g body weight) to sexually mature male tilapia significantly increased kiss2 and gnrh1 mRNA levels at 24 hr post injection (P < 0.001), while the treatment with an anti-thyroid, MMI (100 ppm for 6 days) significantly reduced kiss2 and gnrh1 mRNA levels (P < 0.05). gnrh2, gnrh3 and thyrotropin-releasing hormone mRNA levels were insensitive to the thyroid hormone manipulations. Furthermore, RT-PCR showed expression of thyroid hormone receptor mRNAs in laser-captured GnRH neurons but not in kiss2 neurons. This study shows that GnRH1 may be directly regulated through thyroid hormone, while the regulation of Kiss2 by T3 is more likely to be indirect.